2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26191
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Incorporating Designer Empathy in Senior Capstone Design Courses

Abstract: Design and Engineering). His engineering design research focuses on developing computational representation and reasoning support for managing complex system design. The goal of Dr. Morkos' research is to fundamentally reframe our understanding and utilization of system representations and computational reasoning capabilities to support the development of system models which help engineers and project planners intelligently make informed decisions at earlier stages of engineering design. On the engineering edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Empathic design is valued for "empower[ing] designers by observation" [21]. Schmitt et al reported pedagogical strategies in two capstone design courses that were said to enhance student designers' empathy [22]. The paper starts by grounding the need of empathy in the gap between the engineering designers and their users, noting that empathy "is particularly important in engineering education where students may be of different demographics than those they will ultimately design for."…”
Section: Empathic In Deedmentioning
confidence: 99%
See 1 more Smart Citation
“…Empathic design is valued for "empower[ing] designers by observation" [21]. Schmitt et al reported pedagogical strategies in two capstone design courses that were said to enhance student designers' empathy [22]. The paper starts by grounding the need of empathy in the gap between the engineering designers and their users, noting that empathy "is particularly important in engineering education where students may be of different demographics than those they will ultimately design for."…”
Section: Empathic In Deedmentioning
confidence: 99%
“…However, this focus on the empathizer's (designer's) inner life did not translate into pedagogical practice in the capstone projects, where empathy was once again operationalized as an instrument for data collection. Speaking of the projects-designing for users with disability, the authors concluded, "[r]egular exposure to handicapped users, their limitations, and how these impact their ability to perform daily tasks, can provide useful data" [22].…”
Section: Empathic In Deedmentioning
confidence: 99%
“…Students did an accessibility simulation to promote empathetic design, and interacted with the customer five different times throughout the semester. Other authors have looked at developing empathy during capstone design [6] as well as an in ethics courses [7]. This work builds upon prior research by trying to understand which constructs of empathy are most impacted by a rehabilitation engineering course, as well as which course activities seemed to have the highest impact on students' development of empathy.…”
Section: Prior Researchmentioning
confidence: 99%
“…This module could possibly be used to engender empathy for individuals with disabilities within engineering students. Schmitt and colleagues described how they have used design projects to achieve this focusing on user-inclusive design [24]. Learning outcomes specific to developing empathy could be integrated into future iterations of this module or similar modules.…”
Section: Future Directionsmentioning
confidence: 99%